2015
DOI: 10.1103/physrevd.91.124033
|View full text |Cite
|
Sign up to set email alerts
|

PVcriticality in the extended phase space of black holes in massive gravity

Abstract: We study the P -V criticality and phase transition in the extended phase space of charged anti-de Sitter black holes in canonical ensemble of ghost-free massive gravity, where the cosmological constant is viewed as a dynamical pressure of the black hole system. We give the generalized thermodynamic first law and the Smarr relation with massive gravity correction. We find that not only when the horizon topology is spherical but also in the Ricci flat or hyperbolic case, there appear the P -V criticality and pha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
201
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(207 citation statements)
references
References 30 publications
6
201
0
Order By: Relevance
“…Also, the existence of Van der Waals like behavior in extended phase space has been addressed in ref. [62]. Moreover, the generalizations of such theory to include nonlinear electrodynamics, higher derivative gravity and gravity's rainbow have been done [63][64][65][66].…”
Section: Jhep05(2016)029mentioning
confidence: 99%
“…Also, the existence of Van der Waals like behavior in extended phase space has been addressed in ref. [62]. Moreover, the generalizations of such theory to include nonlinear electrodynamics, higher derivative gravity and gravity's rainbow have been done [63][64][65][66].…”
Section: Jhep05(2016)029mentioning
confidence: 99%
“…In fact, the same form (Eq. (12)) can also be found in different black hole systems [8,9], and we can also obtain ρ c = 3/8 withα = 1/α.…”
Section: The Generalization Of Black Hole Specific Volume and Numentioning
confidence: 79%
“…For charged AdS black hole, it was found that the transition is of the Van der Waals (vdW) type in the canonical ensemble [4,5]. Recently, by treating the cosmological constant as the pressure, P = −Λ/8π [6,7], the complete analogy between the vdW fluid and charged AdS black hole was found, which is a great success in studying phase transition of black holes and investigations in different black hole systems have been carried out [8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermodynamics of black holes in massive gravity are studied in [55,56], here we list the temperature, entropy and thermodynamics volume in each horizon…”
Section: D Ds Black Hole In Massive Gravitymentioning
confidence: 99%